Determining the factors affecting the development of perioperative complications according to aging stages - ZENGİN, SENİYYE ÜLGEN; ORHON ERGÜN, MELİHA; ÇORMAN DİNÇER, PELİN; UMUROĞLU, TÜMAY (My University, 2022)
Objective: This study aimed to examine perioperative complication risks in elderly patients stratified by age. Method: Elderly patients (youngest-old, ages 65 to 74 years; middle-old, 75 to 84 years; and oldest-old, ≥85 years) and controls (20-30 years) who underwent surgical intervention under general anesthesia were included in this prospective observational study. Results: Two-hundred-sixty patients were included. Different age subgroups showed a different course in terms of perioperative complications. For any combined end-point of any perioperative complication, having a body mass index>28 [odds ratio (OR): 2.4; 95% confidence interval (CI): 1.2-4.6; p=0.012] and being on multi-pharmacy regimen at baseline (OR: 1.9; 95% CI: 1.1-3.5; p=0.029) emerged as significant independent predictors. In reference to controls, each elderly age group emerged as a significant independent predictor: youngestolds (OR: 4.9; 95% CI: 2.2-10.8; p<0.001); middle-olds (OR: 2.5; 95% CI: 1.1-5.4; p=0.025); oldest-olds, (OR: 5.6; 95% CI: 2.5-12.6; p<0.001). Conclusion: Elderly patients appear to have higher risk for intraoperative and postoperative complications when compared to the young patients, and each age group appears to have increased risk for different type of complications.

Amaç: Bu çalışma yaşa göre katmanlara ayrılmış yaşlı hastalarda perioperatif komplikasyon risklerini incelemeyi amaçlamıştır. Yöntem: Bu prospektif gözlemsel çalışmaya, genel anestezi altında cerrahi girişim yapılan yaşlı hastalar (yaşlı hastalar, 65-74 yaş; ileri yaşlı hastalar, 75-84 yaş; ve çok ileri yaşlı hastalar, ≥85 yaş) ve kontrol grubu (20-30 yaş) dahil edilmiştir. Bulgular: İki yüz altmış hasta çalışmaya dahil edilmiştir. Farklı yaş alt grupları perioperatif komplikasyonlar açısından farklı seyir göstermiştir. Herhangi bir komplikasyon olması şeklindeki kombine sonlanım noktası için, vücut kitle indeksi>28 olması [olasılık oranı (OO): 2,4; %95 güven aralığı (GA): 1,2-4,6; p=0,012] ve başlangıçta çoklu ilaç kullanıyor olmak (OO: 1,9; %95 GA: 1,1-3,5; p=0,029) anlamlı bağımsız belirleyiciler olarak bulunmuştur. Kontrollere göre, her bir yaşlı alt grubunda bulunmak anlamlı bağımsız belirleyici olarak saptanmıştır: Yaşlılar (OO: 4,9; %95 GA: 2,2-10,8; p<0,001); ileri yaşlılar (OO: 2,5; %95 GA: 1,1-5,4; p=0,025); çok ileri yaşlılar (OO: 5,6; %95 GA: 2,5-12,6; p<0,001). Sonuç: Genç hastalarla karşılaştırıldığında, yaşlı hastalar intraoperatif ve postoperatif komplikasyonlar açısından yüksek risk altında görünmektedir ve her bir yaş grubunun farklı tip komplikasyonlar için riski artmıştır.
Yaşlılık evrelerine göre perioperatif komplikasyon gelişimine etki eden faktörlerin belirlenmesi
Keywords: Complications; elderly; middle-old; surgery; oldest-old; youngest-old; Cerrahi; çok ileri yaşlı; ileri yaşlı; komplikasyonlar; yaşlı; yaşlılar